Impact of Work Life Balance, Workload and Supervisory Support on Teachers’ Job Performance in Private Institutions of Islamabad - Qazi Abdul Subhan, Sana Rashid, Abdullah Hafeez, (JELM, 2023)
Innovative assessments that allow students to manipulate data and role play are currently being produced using the CBT method. But when not properly designed, students could lose their interest in adopting it.